Investigation of loose wood chips and sawdust as alternative sustainable sound absorber materials. (15th January 2021) - Boubel, Ayoub; Garoum, Mohammed; Bousshine, Said; Bybi, Abdelmajid
Highlights: Experimental investigation of the acoustic absorption of red, and beechwood chips. Inverse estimation of eight non-acoustical parameters involved in(JCAPL) model. Redwood chips with fabric used to simulate the intelligibility of a conference room. Abstract: This work deals with an experimental investigation of the acoustic absorption of two kinds of materials, i.e. chips, and sawdust of red, and beechwood. For this purpose, several particle sizes classes, and thicknesses were tested in the impedance tube in the frequency range [50–1400] Hz. The results show that the classes of (0.31 mm−0.63 mm), (0.63 mm−1.25 mm), and (1.25 mm−2.5 mm) give a better absorption coefficient, while the classes equal or higher than (5 mm−8 mm) as well as the class (0.16 mm–0.315 mm) are the least efficient ones. Also, one of the best particle sizes, namely (1.25 mm-2.5 mm) from redwood was packaged in a piece of fabric and then used as an alternative absorbent panel to simulate the intelligibility parameters of a large conference room of 1220 m 3 in the interval [50–6000] Hz. The influence of the fabric on the absorption coefficient was examined first, and then the measurements of the absorption coefficient have been extended up to 6000 Hz by calculation after estimating the all 8 non-acoustical parameters involved in the Johnson-Champoux-Allard-Pride-Lafarge (JCAPL) model. The comparison between the intelligibility parameters obtained with our panels, and those which we simulated using commercial perforated panels, shows that they are almost the same. Consequently, the proposed alternative solution allowed us to reduce the project's budget compared to the situation where the classic perforated wood panels were utilized.